Inequalities in Argentine secondary school: recognition and enjoyment of learning (Praxis Educativa, 2023)
The article addresses the relationship between school experience, emotions, and inequality in Argentine secondary schools. The student school experience in secondary school change policies (Re-entry Schools, City of Buenos Aires; PROA, in the province of Córdoba) is reconstructed, observing emotions, the bond with their teachers, and the place of knowledge and learning. In both policies, the experience is pleasant, but when disaggregating said emotionality, differential ways of guaranteeing the right to secondary education are glimpsed. On re-entry, a recognition link is mainly built; At PROA, academics and enjoyment of learning are emphasized, but with selected young people who have a relationship with knowledge close to the school proposal.
Keywords: Argentina; secondary education; social inequality; emotional experience; Sociology of education